Efektivitas Pupuk Kandang Kambing dan Pupuk Organik Cair dari Limbah Kulit Kopi terhadap Pertumbuhan Stek Kumis Kucing (Orthosiphon Aristatus) - Restu Bremana Tarigan; Najla Lubis; Desi Sri Pasca Sari Sembiring (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
This study aims to determine the effectiveness of goat manure and liquid organic fertilizer made from coffee husk waste on the growth of Java tea (Orthosiphon aristatus) cuttings. The study used a factorial Randomized Block Design (RBD) consisting of two factors with 48 plots. The first factor was the application of goat manure, symbolized as “S,” with four treatment levels: S0 (without goat manure), S1 (250 g/polybag), S2 (350 g/polybag), and S3 (450 g/polybag). The second factor was the application of liquid organic fertilizer made from coffee husk waste, symbolized as “K,” with four treatment levels: K0 (0 ml/L water/polybag), K1 (30 ml/L water/polybag), K2 (60 ml/L water/polybag), and K3 (90 ml/L water/polybag). Thus, there were 16 treatment combinations with three replications. The parameters observed in this study were the time of shoot emergence, number of shoots, shoot length, number of leaves, plant height, and survival percentage. The results showed that the application of goat manure and liquid organic fertilizer from coffee husk waste on the growth of Java tea (Orthosiphon aristatus) cuttings had no significant effect on all observed parameters.